Benzenediazonium ion derived from Sudan I forms an 8-(phenylazo)guanine adduct in DNA - Stiborová, M; Asfaw, B; Frei, E; Schmeiser, H H; Wiessler, M (Chemical research in toxicology, 1995)
1-(Phenylazo)-2-hydroxynaphthalene (Sudan I, Solvent Yellow 14) is a liver and urinary bladder carcinogen in mammals. Sudan I forms benzenediazonium ion during cytochrome P-450 catalyzed metabolism. Calf thymus DNA was reacted with Sudan I activated by microsomal enzymes or with benzenediazonium ion in vitro, and the adducts formed were analyzed by the 32P-postlabeling technique. Both enrichment procedures (1-butanol extraction and nuclease P1 digestion) of this technique were employed for detection and quantitation of the DNA adducts formed. Cochromatographic analyses of adduct spots obtained by reaction with DNA or homopolydeoxyribonucleotides showed that the major Sudan I-DNA adduct was formed with deoxyguanosine. This adduct was also found in DNA directly reacted with benzenediazonium ion. The major Sudan I-DNA adduct was characterized by UV/vis absorbance spectroscopy as well as by the chromatographic properties of the adduct on cellulose or poly(ethylenimine)--cellulose TLC and HPLC. The characteristics are identical to those of the adduct synthesized from benzenediazonium ion and guanine, identified by mass, UV/vis, and 1H-NMR spectroscopy as 8-(phenylazo)guanine. The results suggest strongly that benzenediazonium ion derived from Sudan I reacts with DNA in vitro to form the stable 8-(phenylazo)guanine adduct.
Keywords: nukleotidy; Microsomes, Liver; Cattle; adukty DNA; Male; Guanine; Adenine; potkani Sprague-Dawley; vysokoúčinná kapalinová chromatografie; skot; adenin; techniky in vitro; naftoly; mužské pohlaví; Naphthols; Chromatography, High Pressure Liquid; krysa rodu Rattus; Spectrophotometry, Ultraviolet; Animals; Nucleotides; Carcinogens; subcelulární frakce; karcinogeny; zvířata; DNA Adducts; In Vitro Techniques; Rats; Diazonium Compounds; guanin; diazoniové sloučeniny; jaterní mikrozomy; spektrofotometrie ultrafialová; Rats, Sprague-Dawley; Subcellular Fractions